ENVIRONMENTAL IDENTITY AS A PREDICTOR OF DIGITAL PRO-ENVIRONMENTAL BEHAVIOR: A STUDY OF DIGITAL CARBON FOOTPRINT AWARENESS AMONG GENERATION Z - Julian Amriwijaya (ADISAM Publisher, 2026)
The rapid development of digital technology has driven an increase in online activities that indirectly contribute to the digital carbon footprint, especially through the use of electronic devices, cloud-based services, and intensive data consumption. Generation Z as the demographic group most familiar with digital technology has a strategic role in encouraging pro-environmental behavior in the digital realm. This study aims to examine the role of environmental identity as a predictor of digital pro-environmental behavior, with a focus on digital carbon footprint awareness among Generation Z. The method used is a systematic literature review of scientific articles, academic books, and research reports relevant to the topics of environmental identity, digital pro-environmental behavior, and environmental awareness of Generation Z. The results of the study indicate that a strong environmental identity contributes significantly to increasing individual awareness and engagement in environmentally friendly digital behavior, such as managing digital energy consumption, selecting sustainable platforms, and reducing non-essential digital activities. In addition, the literature also confirms that personal values, social norms, and digital environmental literacy play a mediating role in the relationship between environmental identity and digital pro-environmental behavior. This research provides a conceptual contribution in broadening the understanding of pro-environmental behavior in the digital era and serves as a basis for developing educational strategies and policies oriented towards reducing the environmental impact of Generation Z's digital activities.